PERAN STRATEGI KEPEMIMPINAN BIAYA MEMEDIASI ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA - Krisna, Gede Andika; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 9 No 11 (2020), 2020)
The purpose of this study is to explain the role of cost leadership strategies mediating the effect of entrepreneurial orientation and market orientation on Dodol Business performance in Buleleng Regency. This research was conducted at Dodol Enterprises in Buleleng Regency. The sample size taken was 160 Dodol Enterprises, using (census). Data collection using a questionnaire. Analysis techniques using Structural Equation Modeling (SEM). The results of the analysis show: 1) Market orientation and entrepreneurial orientation have a positive and significant effect on business performance, 2) market orientation, entrepreneurial orientation have a positive and significant effect on the cost leadership strategy, 3) the cost leadership strategy has a positive and significant effect on business performance, 4) Cost leadership strategies partially mediate the effect of entrepreneurial orientation and market orientation on business performance. Keywords: business performance, entrepreneurial orientation, market orientation, cost leadership strategy